KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP TINGAT KEPUASAN PELANGGAN PADA BIMBINGAN BELAJAR PALEM V - Simatupang, Lucy Nancy; Karimah, Nasikhatul (Jurnal Manajemen, 2024)
ABSTRACT This study aims to determine the effect of service quality, price, and location on customer satisfaction at Palem V tutoring simultaneously or partially. The data used is primary data collected through the distribution of questionnaires to 100 respondents who joined the Palem V Tutoring. The quantitative method and the results of this study are based on the answers of respondents using a Likert scale. The analytical method used in this research is Instrument Test (Validity and reliability), Basic Normality Test, Classical Assumption Test (Normality, Multicollinearity, Autocorrelation, Heteroscedasticity), Hypothesis Test (Multiple linear regression analysis, F test, t test and Coefficient of Determination) . The results of this study indicate that Service Quality, Price, and Location by F Test (simultaneous) have an effect on and significant to Customer Satisfaction, and the results of the t-test (partial) Service Quality (X1) and Price (X2) have an effect and significant to Customer Satisfaction (Y ) while Location (X3) has no effect and is not significant on Customer Satisfaction (Y).